Regional air quality in Leipzig, Germany: detailed source apportionment of size-resolved aerosol particles and comparison with the year 2000. (26th April 2016) - van Pinxteren, D.; Fomba, K. W.; Spindler, G.; Müller, K.; Poulain, L.; Iinuma, Y.; Löschau, G.; Hausmann, A.; Herrmann, H.
Abstract : A detailed source apportionment of size-resolved aerosol particles in the area of Leipzig, Germany, was performed. Sampling took place at four sites (traffic, traffic/residential, urban background, regional background) in parallel during summer 2013 and the winters 2013/14/15. Twenty-one samples were taken per season with a 5-stage Berner impactor and analysed for particulate mass, inorganic ions, organic and elemental carbon, water-soluble organic carbon, trace metals, and a wide range of organic species. The compositional data were used to estimate source contributions to particulate matter (PM) in quasi-ultrafine (up to 140 nm), accumulation mode, and coarse size ranges using Positive Matrix Factorisation (PMF) receptor modelling. Traffic (exhaust and general traffic emissions), coal combustion, biomass combustion, photochemistry, general secondary formation, cooking, fungal spores, urban dust, fresh sea/road salt, and aged sea salt were all found to contribute to different extents to observed PM concentrations. PMF derived estimates agreed reasonably with estimates from established macrotracer approaches. Quasi-ultrafine PM originated mainly from traffic (20–50%) and photochemistry (30–50%) in summer, while it was dominated by solid fuel (mainly biomass) combustion in winter (50–70%). Tentatively identified cooking aerosol contributed up to 36% on average at the residential site. For accumulation mode particles, two secondary sources typically contributed 40–90% to particle mass. In winter, biomass and coal combustion contributions were up to ca. 25% and 45%, respectively. Main sources of coarse particles were diverse and included nearly all PMF-resolved ones depending on season and air mass origin. For PM10, traffic (typically 20–40% at kerbside sites), secondary formation (30–60%), biomass combustion (10–15% in winter), and coal combustion (30–40% in winter with eastern air mass inflow) were the main quantified sources. At the residential site, contributions from biomass combustion derived up to 60% from local emissions. Coal combustion as a significant source was only present during eastern air mass inflow and showed very similar concentrations at all sites, indicating the importance of trans-boundary air pollution transport in the study area. Overall, nearly half of the PM10 mass was attributed to urban sources by a simple subtractive approach with highest reduction potentials of up to 80% for local (urban) mitigation measures in ultrafine and coarse particles. Local increments of elemental carbon have decreased by about 50% as compared to the year 2000, corroborating results from a former study on the positive effects of a low emission zone, implemented in Leipzig in 2011.